Knowledge and Self-Reported Clinical Approaches Regarding Medication-Related Osteonecrosis of the Jaw Among Final-Year Dental Students, General Dentists, and Specialist Dentists: An Exploratory Cross-Sectional Study - İsmail Çapar; Çiğdem Şeker (Healthcare, 2026)
Background/Objectives: Medication-related osteonecrosis of the jaw (MRONJ) must be recognized promptly by dental professionals at every career stage, yet whether this recognition differs across professional levels remains unclear. This study compared final-year dental students, general dentists, and specialist dentists in terms of their awareness, pharmacological knowledge, and self-reported clinical approaches to MRONJ. Methods: This cross-sectional, exploratory study used a 25-item online questionnaire administered between August and December 2024 to 149 participants (48 students, 51 general dentists, and 50 specialists). Groups were compared using chi-square or Fisher–Freeman–Halton tests, with Benjamini–Hochberg false discovery rate (FDR) correction applied across 79 testable hypotheses; denosumab recognition and routine medication-history questioning were further examined with multivariable logistic regression. Effect sizes were reported as Cramér’s V, and regression results were reported as adjusted odds ratios (aORs) with 95% confidence intervals (CIs). Results: Raw analyses identified 13 comparisons with p < 0.05, of which five remained significant after FDR correction (q < 0.05), all involving recognition of bisphosphonate indications and osteonecrosis-associated agents. After FDR correction, no statistically significant group differences were found for general MRONJ awareness, diagnostic criteria, or self-reported clinical approaches (q > 0.05), and professional status was not independently associated with denosumab recognition or routine medication-history questioning (p > 0.05). Conclusions: Responses regarding MRONJ did not follow a consistent knowledge gradient across professional status; the differences that reached statistical significance were confined to specific items of pharmacological knowledge. These findings need confirmation in larger, representative samples, and future research should look more closely at topic-specific educational needs.